Increased consumption of cardiovascular drugs under volume-based procurement (VBP) policy: demand release or assessment inducing? - Ying Yang; Jieming Zhang; Yuanhui Duan; Lei Zhou; Sisheng Gan; Zongfu Mao; Shaotang Wu; Furong Wang (Health Research Policy and Systems)
Abstract Background The phenomenon of growth in drug consumption within the framework of national volume-based procurement (VBP) policy raises speculations about demand release and policy inducing. This study aims to explore the reasons and mechanisms of drug consumption increases following VBP policy from two perspectives. Methods We collected data from the China Drug Supply Information Platform, National Bureau of Statistics and the Joint Procurement Office. Twenty cardiovascular international non-proprietary names (INNs) in the first three VBP batches and 28 observation regions were included, constructing 418 valid INN-region combinations as the unit for analysis. The average monthly consumption volume of VBP cardiovascular drug was assigned as the explained variable. The generalized difference-in-difference method was conducted using the price reduction level and the size of policy assessment task as the policy intensity indicator. Moderating effect model was employed to examine the role of resident’s income level. Results Increased cardiovascular drug consumption was observed in 285 (68.18%) INN-region combinations after policy implementation. Under VBP policy, the price reduction level was significantly correlated with drug consumption in total (β = 0.144, p < 0.001), as well as in tertiary hospitals, secondary hospitals and primary healthcare centers (PHCs) (all p-values < 0.05). Resident’s income level negatively moderated the impact of price reduction level on drug consumption in total (β = −0.089, p < 0.001) and in secondary hospitals (β = 0.154, p < 0.001) and PHCs (β = −0.2.9, p < 0.001), rather than in tertiary hospitals (β = −0.079, p > 0.05). The size of policy assessment task was positively associated with drug consumption in total (β = 0.052, p < 0.001), as well as in tertiary hospitals, secondary hospitals and PHCs (all p-values < 0.05). Conclusions Two mechanisms codrive drug consumption increases under VBP policy: first is the improvement of cardiovascular medication access and consumption toward lower-income groups following price reduction, pointing to the fulfillment of unmet needs, and second is policy pressure from supporting assessment measures on hospital drug use, indicating potential overprescribing.